2021
DOI: 10.1002/glia.24109
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic VEGFA: An essential mediator in blood–brain‐barrier disruption in Parkinson's disease

Abstract: The integrity of blood–brain‐barrier (BBB) is essential for normal brain functions, synaptic remodeling, and angiogenesis. BBB disruption is a common pathology during Parkinson's disease (PD), and has been hypothesized to contribute to the progression of PD. However, the molecular mechanism of BBB disruption in PD needs further investigation. Here, A53T PD mouse and a 3‐cell type in vitro BBB model were used to study the roles of α‐synuclein (α‐syn) in BBB disruption with the key results confirmed in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…In post-mortem brain tissues of patients with Parkinson’s disease, elevated VEGF-A and nitric oxide levels were detected at sites of astrocytic alpha-synuclein deposition. 22 Inhibition of VEGF-A blocked the deleterious effects of VEGF-A on the blood-brain barrier in a mouse model of Parkinson’s disease, especially among younger mice, suggesting more beneficial effects early in disease pathogenesis.…”
Section: Models To Consider: Parkinson’s Disease and Diabetic Retinop...mentioning
confidence: 99%
“…In post-mortem brain tissues of patients with Parkinson’s disease, elevated VEGF-A and nitric oxide levels were detected at sites of astrocytic alpha-synuclein deposition. 22 Inhibition of VEGF-A blocked the deleterious effects of VEGF-A on the blood-brain barrier in a mouse model of Parkinson’s disease, especially among younger mice, suggesting more beneficial effects early in disease pathogenesis.…”
Section: Models To Consider: Parkinson’s Disease and Diabetic Retinop...mentioning
confidence: 99%
“…Findings indicating angiogenesis in PD are supported by reports showing an upregulation of the pro-angiogenic molecule Vascular Endothelial Growth Factor (VEGF) in the SNpc of PD patients ( Wada et al, 2006 ; Yasuda et al, 2007 ; Lan et al, 2021 ) and non-human primates ( Barcia et al, 2005 ). Increased levels of soluble VEGF receptor-2 and placental growth factor, and lower levels of angiopoietin 2 (an anti-angiogenic molecule) were detected in the CSF of PD patients ( Janelidze et al, 2015 ).…”
Section: Vascular Changes In Parkinson’s Diseasementioning
confidence: 76%
“…A study using the A53T PD mouse model showed that the expression of tight junction-related proteins at the BBB decreased leading to increased vascular permeability ( Lan et al, 2021 ). When we examined the temporal dynamics of BBB leakage in another progressive α-syn-PD mouse model ( Elabi O. et al, 2021 ), we detected significant extravascular fibrinogen accumulation already at the early stage preceding behavioral deficits ( Elabi O. et al, 2021 ).…”
Section: Vascular Changes In Parkinson’s Diseasementioning
confidence: 99%
“…Alternatively, the antibodies might recognize different aSyn cleavage products, conformations or aggregation forms such as oligomers of different sizes, protofibrils and fibrils. Indeed, oligomeric aSyn has been observed in reactive astrocytes in the A53T PD mouse model and related to blood–brain-barrier disruption [ 81 ]. Also in human PD brain, aSyn-immunoreactive astrocytes have been observed [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%